Explicit and Implicit Biases in Students' Skin Colours Aesthetic Preferences - Giovanni Perillo; Stefano Mastandrea (LED Edizioni Universitarie, 2022)
Several tools have been employed to detect the emergence and development of racial stereotypes and prejudices among little children and adolescents. In our study, we confront some of these tools, and present the results of the Skin Colours Test. In its specificity, the Skin Colours Test proposes a change in the object of investigation (appreciation of the homogeneity or heterogeneity of colours) and aims to detect explicit and implicit stereotypes and prejudices of boys and girls regarding aesthetic choices (even neutral choices) concerning skin colours. Sample: one group of 129 (64 F) students (M = 12.31), almost all of Italian descent, and another group of 129 (62 F) students (M = 12.36), less than 30% of different descents. Method: three pictures, each made up of 16 skin colours, were shown and students were asked to vote on their aesthetic preference between homogeneity or heterogeneity of skin colours and to give reasons for these choices. Main results: the motivations for some choices that preferred skin colour heterogeneity (neutral choice) over homogeneity, brought out stereotypes and biases. In addition, we consider the contextual specificities that the Skin Colours Test detects as crucial in order to detect specific educational needs and structure targeted educational interventions.